2009
DOI: 10.2459/jcm.0b013e32831967b2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial abnormalities underlying persistent ST-segment elevation after anterior myocardial infarction

Abstract: Persistent ST-segment elevation after anterior myocardial infarction is related to a larger extent of transmural necrosis and persistent microvascular damage as assessed by contrast-enhanced magnetic resonance imaging. However, the presence of microvascular damage seems to be the most powerful determinant of persistent ST-segment elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…[24] Persistent ST-segment elevation probably indicates the presence of persistent microvascular damage, but its fundamental mechanism remains to be clarified. [25] A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[24] Persistent ST-segment elevation probably indicates the presence of persistent microvascular damage, but its fundamental mechanism remains to be clarified. [25] A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is typically located on the anterior wall in the territory of the left anterior descending artery. It occurs in 5% of patients with a recent ST-segment elevation myocardial infarction,but has also been reported in patients with hypertrophic cardiomyopathy and Chagas disease 13…”
Section: Discussionmentioning
confidence: 95%
“…32,33 Although the exact mechanism for its persistence has yet to be elucidated, at least one study has shown that continued ST-segment elevation may be a further marker of extensive transmural necrosis and microvascular damage. 34 Because of the typical location of ventricular aneurysm postinfarction, ST-segment elevation in this setting is most commonly in the anterior leads. 35 Historical factors, such as known recent AMI, should help provide the emergency physician some clues in distinguishing an acute STEMI from ventricular aneurysm.…”
Section: Ventricular Aneurysmmentioning
confidence: 99%